Comprehensive analysis of lncRNA expression profiles in cytopathic biotype BVDV-infected MDBK cells provides an insight into biological contexts of host–BVDV interactions. Issue 1 (1st January 2021) - Gao, Xuwen; Niu, Chao; Wang, Zhuo; Jia, Shuo; Han, Meijing; Ma, Yingying; Guan, Xueting; Wang, Li; Qiao, Xinyuan; Xu, Yigang
ABSTRACT: Bovine viral diarrhea virus (BVDV) is the causative agent of bovine viral diarrhea-mucosal disease, which significantly affects the production performance of cattle, causing serious economic losses to the cattle industries worldwide. Up to now, some mechanisms involved in host–BVDV interaction are still not fully understood. The discovery of long non-coding RNAs (lncRNAs) has provided a new perspective on gene regulation in diverse biological contexts, particularly in viral infection and host immune responses. However, little is known about the profiles and functions of lncRNAs in host cells in response to BVDV infection. Here, we utilized Illumina sequencing to explore lncRNAs profiles in cytopathic (CP) biotype BVDV-infected MDBK cells to further reveal the potential roles of lncRNAs in BVDV infection and host–BVDV interaction with integrated analysis of lncRNAs and mRNA expression profiles. A total of 1747 significantly differentially expressed genes, DEGs (156 lncRNAs and 1591 mRNAs) were obtained via RNA-seq in BVDV-infected MDBK cells compared to mock-infected cells. Next, these DE lncRNAs and mRNAs were subjected to construct lncRNAs-mRNAs co-expression network followed by the prediction of potential functions of the DE lncRNAs. Co-expression network analysis elucidated that DE lncRNAs were significant enrichment in NOD-like receptor, TNF, NF-ĸB, ErbB, Ras, apoptosis, and fatty acid biosynthesis pathways, indicating that DE lncRNAs play important roles in host–BVDV interactions. Our data give an overview of changes in transcriptome and potential roles of lncRNAs, providing molecular biology basis for further exploring the mechanisms of host–BVDV interaction.